Combined fluticasone furoate/vilanterol reduces decline in lung function following inhaled allergen 23 h after dosing in adult asthma: a randomised, controlled trial - Oliver Amanda; Quinn Dean; Goldfrad Caroline; van Hecke Benjamin; Ayer Jonathan; Boyce Malcolm (Clinical and Translational Allergy, 2012)
Abstract Background There is a need for preventative asthma maintenance therapy that provides lasting bronchoprotection against allergen provocation. Fluticasone furoate (FF) is a novel inhaled once-daily corticosteroid, being investigated as monotherapy for asthma and in combination with vilanterol (VI), a novel inhaled once-daily long-acting beta-agonist, for asthma and chronic obstructive pulmonary disease. Methods In a crossover study of 52 subjects with mild asthma, FF/VI 100/25mcg and FF 100 dosed once-daily in the evening for 28 days were compared with placebo to evaluate their capacity to provide bronchoprotection against the early asthmatic response (EAR) stimulated by an inhaled allergen challenge. Bronchoprotection was assessed by change from post-saline baseline in weighted mean (wm) forced expiratory volume in 1 s (FEV1) for the first 2 h post-allergen challenge, which was on Day 29 (22–23 h post final dose on Day 28). The EAR was also assessed using maximum percent decrease from post-saline baseline and minimum absolute FEV1; the incidence of adverse events was a secondary endpoint. Results FF/VI 100/25 and FF 100 both provided significant bronchoprotection against the EAR for all endpoints assessed. For wmFEV1 over the first 2 h post-allergen challenge, a 162 mL (95% CI, 87 to 237 mL) difference was observed between placebo and FF 100, while a 145 mL (95% CI, 69 to 222 mL) difference was observed between placebo and FF/VI 100/25 treatment. No difference between active treatments was observed (−17 mL; 95% CI, –91 to 57 mL). Both treatments were well tolerated. Conclusions FF 100 alone and in combination with VI 25 provides significant bronchoprotection against the EAR in subjects with mild asthma. That this protection is provided at the trough of dosing, i.e. 23 h post last dose, supports the utility of FF 100 and FF/VI 100/25 as viable once-daily therapies. Trial registration Clinicaltrials.gov identifier: NCT01128569, GSK Study number: HZA113090